1996
DOI: 10.1007/bf00144419
|View full text |Cite
|
Sign up to set email alerts
|

Results of a questionnaire about nurse students' smoking habits and knowledges in an Italian teaching school of nursing

Abstract: Six-hundred and sixty-two nurse students (aged 25.2 +/- 4.11 years; 153 were males) answered a self-administered, anonymous questionnaire about smoking habits and knowledges in a large urban Teaching School of Nursing. The overall response rate was 88%. Current smokers were 336 (51%), former smokers 80 (12%). Nurse students claimed to know the dangers of tobacco and nurse training seemed to modify the preferential source of information about tobacco smoking towards medical fonts; however, only a quarter of nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The intervention had no effect on nicotine dependence levels, which rose on both campuses in the way described by Boccoli [25]. The low initial dependence levels as compared with those recorded in similar studies concerning health science students [4,21,[26][27][28] may have hindered the good results of the intervention, together with the fact that it was not designed for this end.…”
Section: Discussionmentioning
confidence: 79%
“…The intervention had no effect on nicotine dependence levels, which rose on both campuses in the way described by Boccoli [25]. The low initial dependence levels as compared with those recorded in similar studies concerning health science students [4,21,[26][27][28] may have hindered the good results of the intervention, together with the fact that it was not designed for this end.…”
Section: Discussionmentioning
confidence: 79%
“…Our study represents one of the first investigations of tobacco smoking ever conducted among a complete cross‐section of Australian nursing students. Although there is little cross‐sectional data of this nature from Australia, similar studies have been conducted among nursing students in other countries (Carmichael & Cockcroft, 1990; Blakey & Seaton, 1992; Najem et al ., 1995; West & Hargreaves, 1995; Boccoli et al ., 1996; Charlton et al ., 1997; Ahmadi et al ., 2004; Baron‐Epel et al ., 2004; Krommydas et al ., 2004; Sekijima et al ., 2005; Suzuki et al ., 2005). The examination of previous research conducted among student nurses suggests a number of important issues with regard to smoking prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Another Japanese study also documented a high smoking rate during their research (24%) (Suzuki et al ., 2005). The highest smoking rates of all appear to have been documented some years ago in Italy (Boccoli et al ., 1996) and the UK (Carmichael & Cockcroft, 1990), where about half of the nursing students surveyed at the time were current users of tobacco (51% and 43%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultural differences which are shown in the international literature on smoking in nursing staff illustrate the difficulty of importing policy solutions from one country to another. Surveys of student nurses in Italy revealed that 40–50% of student nurses were current smokers (Boccoli et al . 1996), and that nursing students were more likely to smoke than medical students (Melani et al .…”
Section: Introductionmentioning
confidence: 99%